Membangun Semangat Melanjutkan Pendidikan Melalui Seminar Motivasi Belajar - Hakim, Rafi Wildzan; Ernawati; Afiah, Dafa; Maulida, Zulfa; Al Imani, Muhammad Nasim Adil; Izaanatulhaqq, Ziyaan; Karim, Arifin A. Abd. (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2024)
The community service activity in the form of a Learning Motivation Seminar was carried out by KKN students from Nahdlatul Ulama Indonesia University at SD Negeri Gadog 02, Sukajadi Village, involving 86 fourth-grade students. The program aimed to enhance students' motivation to pursue higher education. The low interest in continuing education was the main issue, prompting the KKN MD-V-03 group to organize this seminar. The methods used included initial observations, presentations, interactive discussions, as well as games and simulations to increase student participation. As a result, the students showed increased motivation, marked by their active engagement and courage in presenting their aspirations. This seminar not only provided short-term benefits but also motivated students to continue their education to higher levels. In conclusion, this program successfully boosted students' learning enthusiasm and raised awareness of the importance of education.